Anticardiolipin Antibodies in Patients with Chronic Hepatitis C Virus Infection: Characterization in Relation to Antiphospholipid Syndrome - Ordi-Ros, Josep (American Society for Microbiology, 2000)
The antiphospholipid syndrome (APS) is usually defined by the association of clinical manifestations that comprise venous and/or arterial thrombosis, recurrent fetal losses, and thrombocytopenia, along with the presence of anticardiolipin (aCL) antibodies and/or lupus anticoagulant. Various infectious diseases can induce aCL; however, these antibodies are not usually associated with thrombotic events, as happens with autoimmune diseases, in which these antibodies need the presence of β(2)-glycoprotein I. Levels of immunoglobulin G (IgG) and IgM aCL antibodies were determined by enzyme-linked immunosorbent assay for 243 patients with chronic hepatitis C virus (HCV) infection and 100 healthy controls. Clinical events of APS, the level of β(2)-glycoprotein dependence of aCL, the presence of cryoglobulins and other autoantibodies, and cross-reactivity between purified aCL and HCV were evaluated. Positive results for aCL antibodies were found more frequently (3.3%) for the patients with HCV infection than for healthy controls (0%). All positive aCL antibodies were β(2)-glycoprotein I independent. No significant association was found between aCL antibodies and clinical manifestations of APS, neither was one found between the presence of other autoantibodies or cryoglobulins and that of aCL. Finally, no cross-reactivity between aCL antibodies and HCV antigens was observed. As previously reported, aCL antibodies seem to be an epiphenomenon, and they do not have clinical or laboratory significance in HCV patients.